KEEFEKTIFAN MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR IPAS SISWA PADA MATERI RANTAI MAKANAN KELAS V DI SDN SINDANG 01 KAB TEGAL: Penelitian Kuantitatif - Zyan Fadlika Maula Kusuma Fadlika; Arfilia Wijayanti; Bagus Ardi Saputro (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The implementation of learning in the classroom by the teacher greatly influences the active learning process and the achievement of student learning outcomes. At the time of the initial interview, there were still 55% of students whose learning outcomes had not yet been completed. The problem of this research is "The Effectiveness of the Project Based Learning Model on Students' Science and Science Learning Outcomes in Class V Food Chain Material at SDN Sindang 01, Tegal Regency". The aim to be achieved in this research is to examine the effectiveness of the Project Based Learning Model on Student Science Learning Outcomes in Class V Food Chain Material at SDN Sindang 01 Tegal Regency. This type of research is quantitative research with quantitative experimental methods and uses a Pre Experimental Designs research design in the form of One-Group Preset-Posttest Design. The population of this study was all 20 class V students. The results of the research that has been carried out can be concluded that the Project Based Learning learning model is effective on student learning outcomes in science subjects. This research measured students' learning outcomes in science subjects when following the learning process or Pretest Posttest. Based on the discussion of the results of research conducted at SD Negeri Sindang 01, Dukuhwaru District, Tegal Regency, it can be concluded that it is effective for the learning outcomes of the science and science subjects. Research is measured by students' learning outcomes in science subjects when participating in learning activities or administering pretest-posttest. Based on calculations, the results of the pretest show an average of 25% and the results of the posttest show an average of 85%. So students experience an increase of 60% from the predetermined KKM, namely 70. If the class completion percentage is >70% then it has been completed and if the class completion percentage is <70% then it has not been completed. With this treatment, it can make it easier for students to understand the material, improve the material, explore creativity and improve student learning outcomes. It can be concluded that the effectiveness of the Project Based Learning model on students' science learning outcomes in class V food chain material at SD Negeri Sindang 01 is effective on scienceas learning outcomes.